Hugh MacDiarmid's Epic Poetry - Riach, Alan (Edinburgh University Press, 2001)
A collection of Hugh McDiarmid's poetry.
Keywords: MacDiarmid, Hugh, -- 1892-1978 -- Criticism and interpretation.; MacDiarmid, Hugh, -- 1892-1978; Epic poetry, Scottish -- Criticism and interpretation.; Poésie épique écossaise -- Critique et interprétation.; LITERARY CRITICISM / Poetry; Epic poetry, Scottish; Criticism, interpretation, etc.